The Existence Legal Certainty of the Truth and Reconciliation Commission in Indonesia - Safrin Salam; Rizki Mustika Suhartono (Faculty of Law, Musamus University, 2020)
Indonesia is a country that has a history of gross human rights violations. However, the case has not been resolved. In addition to settlement through the court, a reconciliation pattern is highly recommended in the settlement of the case in question. But the rules on reconciliation have been canceled by the Constitutional Court. The results of the study concluded that the Settlement of cases of gross human rights violations was resolved with a pattern of reconciliation with the establishment of an independent institution (KKR). Besides that, the pattern of reconciliation can also be done in a family way. Reconciliation arrangements exist in several regions in Indonesia, namely Papua, Aceh and Palu Reconciliation patterns that exist in these rules vary, there are those who use the TRC pattern there are also those who use family reconciliation patterns.